Evolution of professional ethics courses from web supported learning towards e-learning 2.0 - Zdravkova, Katerina; Ivanović, Mirjana; Putnik, Zoran (Springer, Berlin, Heidelberg, 2009)
Skopje and Novi Sad share several joint courses in Professional Ethics at undergraduate level and at postgraduate level. These courses have been delivered to almost 1000 students from 14 different target groups. For seven years, teaching, learning as well as assessment have been steadily growing from traditional Web supported learning, through blended learning, towards Web 2.0. This paper presents all the stages of the courses evolution using several learning management systems, and the effort to enhance teaching, learning and active contribution of all the actors in the educational process. Particular attention is paid to our latest experience using Moodle and its social networking aspects in education. This survey reveals all the activities during the course delivery including student workload, grading system, and teacher’s efforts to maintain the courses. Student encouraging impressions regarding the content delivery and assessment, their personal opinion about the impact of e-learning 2.0 to quality and quantity of acquired new knowledge, and sincere suggestions to persist in the same direction are the greatest assurance that social networks are currently the best way to deliver computer ethics courses. At the same time, it seems that this approach is the most exhausting and the most challenging for the teachers, but at the same time, the best balance between the effort undertaken and the results obtained.
Keywords: Web supported learning, Blended learning, Social networking.